Pengaruh Penggunaan Gadget Pada Anak Usia Dini Di Masa Pandemi Covid-19 - Machmud, Karmila; A.J. Pauweni, Apriyanto; H Majalia, Asni; Djahara, Windrawati (Jambura Early Childhood Education Journal, 2022)
The purpose of this article is to examine the effect of using gadgets at an early age during the Covid-19 Pandemic. Gadgets are small items that are designed in such a way that electronics are the latest innovations, or can also be said to be truly amazing at their time. The use of electronic learning media does have a very good impact on the learning process during the COVID-19 pandemic as it is today. The name of using gadgets for too long can also have a negative impact at an early age, therefore the role of parents in accompanying their children during the current pandemic is important.